Inflexibility of beliefs and jumping to conclusions in active schizophrenia. (February 2020) - Serrano-Guerrero, Estrella; Ruiz-Veguilla, Miguel; Martín-Rodríguez, Agustín; Rodríguez-Testal, Juan F.
Highlights: What is this? Test, classifies participants with active schizophrenia. Presence/absence of choices influencing decision-making and maintenance of beliefs. Schizophrenia patients made less use of the hints provided by the context. Hastier reasoning and maintenance of original belief in schizophrenia patients. Abstract: Jumping to conclusions (JTC) has been questioned as sufficient cognitive bias for the onset, maintenance, and severity of delusions compared to the bias of inflexibility of beliefs. The WIT ( What is this? ) test was designed to evaluate JTC and its capacity for classifying participants into a group of patients with active schizophrenia and a comparison group. It was also attempted to determine whether the presence/absence of answer choices, considered a measure of induced inflexibility of beliefs, influences decision-making and is related to the tendency to repeat the first decision, or spontaneous inflexibility of beliefs. The sample was made up of 160 participants, 80 patients with schizophrenia diagnosed at hospital admission and 80 healthy controls. The Beads Task and the WIT test were administered. The WIT classified the participants reasonably well (82.7%) compared to the Beads Task (86.3%). The presence of answer choices favored JTC ( d = 0.33), decreasing the number of lines necessary to make a decision ( d = 1.78), and influencing keeping to the original answer ( d = 1.36), in interaction with the group ( d = 0.42). The WIT test overcame some limitations of the Beads Task . The presence/absence of answer choices influenced decision-making and how thinking was flexibilized, more clearly in the case of controls.